CRIMINAL LIABILITY FOR ONLINE SEXUAL EXPLOITATION OF CHILDREN (OSEC) CRIMES IN INDONESIA - Goni, Abdul; Efendi, Dr. Jonaedi (YURIS: Journal of Court and Justice, 2024)
Online Sexual Exploitation of Children (OSEC) has become a global crime in Indonesia during the COVID-19 pandemic. There are difficulties in identifying and investigating perpetrators as they have continued to use technology to enable them to abuse and exploit children, while avoiding detection. This research aims to conceptualize criminal liability for online sexual exploitation of children after the enactment of Law No. 12/2022 on sexual violence. This research method uses an empirical approach, which involves collecting data through observation, interviews, and case studies to identify legal rules, legal principles, and their application in actual cases. Data was collected from various sources including legal documents; police reports; and interviews with legal experts and law enforcers involved in handling OSEC cases. The results of the research indicated that some small-scale cases of sexual exploitation have been found in the Philippines and Thailand, such as sexual grooming, dissemination of child pornographic content, and solicitations by sexting (sending indecent images). In the Philippines, the Thomson Reuters Foundation found cases of live streaming of child sexual abuse. This research is expected to contribute to the development of more comprehensive and effective legal policies in handling online sexual exploitation of children, and increasing the awareness and competence of law enforcement in identifying, investigating and prosecuting perpetrators of OSEC.